The role of local therapy in the treatment of solitary melanoma progression on immune checkpoint inhibition: A multicentre retrospective analysis. (July 2021) - Versluis, Judith M.; Hendriks, Anne M.; Weppler, Alison M.; Brown, Lauren J.; de Joode, Karlijn; Suijkerbuijk, Karijn P.M.; Zimmer, Lisa; Kapiteijn, Ellen W.; Allayous, Clara; Johnson, Douglas B.; Hepner, Adriana; Mangana, Joanna; et al.
Abstract: Introduction: In patients with metastatic melanoma, progression of a single tumour lesion (solitary progression) after response to immune checkpoint inhibition (ICI) is increasingly treated with local therapy. We evaluated the role of local therapy for solitary progression in melanoma. Patients and methods: Patients with metastatic melanoma treated with ICI between 2010 and 2019 with solitary progression as first progressive event were included from 17 centres in 9 countries. Follow-up and survival are reported from ICI initiation. Results: We identified 294 patients with solitary progression after stable disease in 15%, partial response in 55% and complete response in 30%. The median follow-up was 43 months; the median time to solitary progression was 13 months, and the median time to subsequent progression after treatment of solitary progression (TTSP) was 33 months. The estimated 3-year overall survival (OS) was 79%; median OS was not reached. Treatment consisted of systemic therapy (18%), local therapy (36%), both combined (42%) or active surveillance (4%). In 44% of patients treated for solitary progression, no subsequent progression occurred. For solitary progression during ICI (n = 143), the median TTSP was 29 months. Both TTSP and OS were similar for local therapy, ICI continuation and both combined. For solitary progression post ICI (n = 151), the median TTSP was 35 months. TTSP was higher for ICI recommencement plus local therapy than local therapy or ICI recommencement alone (p = 0.006), without OS differences. Conclusion: Almost half of patients with melanoma treated for solitary progression after initial response to ICI had no subsequent progression. This study suggests that local therapy can benefit patients and is associated with favourable long-term outcomes. Highlights: After treatment of solitary melanoma progression, 44% had no subsequent progression. Solitary progression is not necessarily the harbinger of widespread progression. Local therapy of solitary progression may contribute to favourable long-term outcomes.